Genome-wide SNP identification and annotation from high coverage whole genome sequenced data of Bhadawari buffalo - Ameya Santhosh, Vikas Vohra, Rani Alex and Gopal Gowane (Indian Journal of Dairy Science, 2024)
Eukaryotic genomes are rich in Single Nucloetide Polymorphisms(SNPs) which have gained immense importance as the genetic marker of choice especially for the production traits in livestock species. The high throughput sequencing technologies, which offer the quick and greater coverage genome sequencing data has improved the accuracy of SNP discovery through various bioinformatic pipelines. This is the preliminary study to uncover the SNPs from high coverage (45x) sequenced data of the unique Bhadawari buffalo breed of India. Blood was collected from two pure bred animals from the breeding tract and DNA was sequenced using Illumina Highseq technology. The sequences were aligned to the buffalo reference genome and variant calling was done.The variant count (SNPs, Insertions, and deletions) discoverable at six ascending read depths (2,5,10, 20, 30 and 40) has been analysed. The Transition to Transversion ratio (Ti/Tv ratio) is found to be nearly 2.2. Chromosome wise distribution of SNPs showed that in all read depths maximum number of SNPs were found to be in the 1st chromosome of Bhadawari buffalo genome.